MEDIA PROMOSI PERPUSTAKAAN PERGURUAN TINGGI DI ERA MILENIAL DAN REVOLUSI INDUSTRI 4.0 - Iqbal, Rahmat; Yunita, Irva (UIN Raden Intan Lampung, 2020)
The era of the industrial revolution 4.0 has begun, libraries are required to provide creativity in delivering information, both information about the availability of new collections or information on library services. This information can use various models of digital promotional media as a means of delivering creative library information such as using websites, social media, and other internet media. In this study using qualitative methods are reviewed through the library research method (Library Research), in strengthening this research the author uses observation and interviews as data collection tools. This study discusses the promotion model used by college libraries, namely using digital media, such as WhatsApp, Facebook, Instagram, and Twitter. These four models are used by college libraries in delivering information to the campus community and aim to increase the interest in visiting and reading by students and lecturers in the library. This information can be in the form of delivery of delayed information, the latest collections in the library, library service information, information on university achievements, and book reviews.